(untitled) (KULT_online, 2022)
Post/Pandemisches Leben. Eine neue Theorie der Fragilität traces the connections between a fragility of life, which has become newly visible as a result of the pandemic, existing dynamics of global inequality, and the exclusionary mechanisms of (post)colonial and hetero-normative structures. With their interdisciplinary theory, the authors succeed in showing the productive potential of fragility for a reflection on a more just post/pandemic society — and oppose to this a politics of the strong.